Factors influencing Malaysian consumers’ intention to use Quick Response (QR) mobile payment - Ibrahim, Muhammad Haidhar; Hussin, Siti Rahayu; Hussin, Siti Haslina (UKM Press, 2019)
In the past decade, conventional payment methods of using cash is progressively replaced with electronic payments. Recently, QR mobile payment begins to receive more attention from many countries including Malaysia. Nevertheless, QR mobile payment is a relatively green area in which very limited literature exists on this subject matter pertaining to consumer acceptance and characteristics of adopter segments of this technology. Therefore, by applying the Technology Acceptance Model (TAM) as the main theoretical framework, the aim of the present study is to investigate the factors influencing intention to use QR mobile payment in Malaysia. Self-administered questionnaires were distributed which resulted in 485 complete responses. Perceived usefulness, personal innovativeness, perceived ease of use, subjective norm, and perceived security were found to be significant in determining intention to use QR mobile payment among Malaysian consumers.